Early prenatal diagnosis of lysosomal storage disorders by enzymatic and molecular analysis. (17th July 2018) - Li, Duan; Lin, Yunting; Huang, Yonglan; Zhang, Wen; Jiang, Minyan; Li, Xiuzhen; Zhao, Xiaoyuan; Sheng, Huiying; Yin, Xi; Su, Xueying; Shao, Yongxian; Liu, Zongcai; et al.
Abstract: Objective: To report the 4‐year experience of early prenatal diagnosis of lysosomal storage disorders (LSDs) at a center in mainland China. Method: Forty‐seven pregnancies affected with LSDs were assed using enzymes and/or molecular studies. Prenatal studies were performed on 43 uncultured chorionic villi (CV) samples, two amniotic fluid samples, and two umbilical cord blood samples. Results: Of the 47 fetuses, 23 (48.9%) were determined to normal, 13 (27.7%) to be carriers, and 11 (23.4%) diagnosed as affected. In this cohort, mucopolysaccharidoses (MPS) type II was the most common LSD, followed by Pompe disease and then metachromatic leucodystrophy. In the 17 MPS II cases, the four affected fetuses showed MPS II enzyme activity expression levels of 1.4% to 6.7%, while the enzyme activity levels of the 13 normal fetuses ranged from 72% to 240.4%. In the seven Pompe cases, three fetuses were normal with Pompe enzyme activity expression levels of 20%, 38.8%, and 77.3%, while four carrier pregnancies showed enzyme activity levels of 17.5%, 17.5%, 33.4%, and 13.8%, respectively. Conclusion: Based on different enzyme properties in uncultured CV, different prenatal diagnostic strategies should be adopted for MPS II and Pompe disease. Combining enzyme assay and molecular studies in uncultured CV improves the reliability of prenatal diagnosis of LSDs. Abstract : What's already known about this topic? Prenatal diagnosis of lysosomal storage disorders (LSDs) can be performed by molecular studies and enzyme assays from uncultured chorionic villi (CV), cultured CV, and cultured amniotic fluid. Enzyme analysis using CV can be confounded by the presence of isoenzymes, pseudodeficiency, and contamination with maternal tissue. There are some reports that indicate that uncultured CV may not be suitable for the prenatal diagnosis of mucopolysaccharidoses (MPS). What does this study add? By direct comparison of molecular studies and enzyme assays, we demonstrate that the use of uncultured CV for MPS is reliable. As the enzyme activity characteristics of each LSD varies in CV, different strategies should be adopted for each LSD to determine the appropriate diagnostic ranges for accurate prenatal diagnosis.